The History of modern fashion from 1850 - Cole, Daniel James; Deihl, Nancy (Laurence King Publishing, 2015)
This illustrated book looks at the history of fashion from 1850 to 2010. Taking a decade-by-decade approach, Daniel James Cole and Nancy Deihl explore the history of fashion as a lively and dynamic manifestation of 20th-century culture. Covering chronological changes in womenswear, menswear and childrenswear, the book looks at the dissemination of style and the mechanisms of change, at the relationship between fashion and the visual, applied and performing arts, the intertwined relationship between fashion and popular culture, the impact of new materials and technology and the growing globalization of style.